ANALISIS KINERJA EJEKTOR UNTUK EKSTRAKSI UAP KONDENSER UTAMA PADA PLTP 25 MW PT GEO DIPA ENERGI Ltd. DIENG - , RAHADIAN KUSUMA ADI PRATAMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Geothermal energy conversioninto electricityatGeoDipa Energy Ltd Dieng power plant use steam from the earth to rotating the turbine.Steam produced in PLTP GeoDipa EnergyLtd. Diengâs wells has wet characteristic. So it, needs to separatethe vapor phase from mixed phaseon theseparator. Steamproducedfromgeothermal wellscontainingnon condensable gases. Non condensablegaseswillgivenegative impactin the condenser. Non condensable gasesshould beremoved because willraise thecondenserpressureanddecrease thegeothermal power plant system eficiency. Cycle Tempo simulation result is verified with PLTP Geo Dipa Energy Ltd Diengâs operation data. From result verification, the difference between steam entering PLTP is 0.004 %. The other variabel verified is cooling water mass flow rate entering main condenser and nett power generated. The difference of both is 1.45 % and 2.875 %. In this research, initialcondenserpressurewas variedtodetermine ejector operating effectto power plant system eficiency. Condenserpressurewas variedfrom0.05 bar-a to 0.1bar-a barwith range per 0.01bar-a. Power plant system eficiency is comparation between nett power generated and maximum power rate entering power plant system, with126.3 MW maximum powerrate entry geothermal power plant. Theoptimal condenser pressureobtainedat0.07bar-a with 19.51 % system efficiency.